The use of tobacco (Nicotiana tabacum Linn.) to control fish louse (Argulus spp.) in Lionhead Goldfish (Carassius auratus Linn.) (Thai) - Silarudee, Somrudee; Waraeksiri, Chakkit; Ruangpanupan, Suchat (Asia-Pacific Journal of Science and Technology, 2017)
Experiments were conducted to study the effect of various levels of tobacco extract (200, 300, 400, and 500 ppm) for the control of the external parasite, fish louse (Argulus spp.) in Lionhead Goldfish (Carassius auratus). A total of 80 fishes were randomly allocated into 4 groups (20 fish in each group). The results showed that the mean release times of Argulus spp. attached to fish which were subjected to different tobacco concentrations of 200, 300, 400 and 500 ppm were 20.49±3.19, 17.48±1.86, 7.87 ±1.71 and 6.94 ±1.87 minutes, respectively. The mean release time at the concentration of 200 ppm was highly significantly longer than that of 300, 400 and 500 ppm (P<0.01). Despite its longer release-time, the use of tobacco at 200 ppm seems to be the best and safest concentration for the control of Argulus spp. in Goldfish.